Functional outcomes among survivors of pediatric in-hospital cardiac arrest are associated with baseline neurologic and functional status, but not with diastolic blood pressure during CPR. (October 2019) - Wolfe, Heather A.; Sutton, Robert M.; Reeder, Ron W.; Meert, Kathleen L.; Pollack, Murray M.; Yates, Andrew R.; Berger, John T.; Newth, Christopher J.; Carcillo, Joseph A.; McQuillen, Patrick S.; Harrison, Rick E.; Moler, Frank W.; et al.
Abstract: Aim: Diastolic blood pressure (DBP) during cardiopulmonary resuscitation (CPR) is associated with survival following pediatric in-hospital cardiac arrest. The relationship between intra-arrest haemodynamics and neurological status among survivors of pediatric cardiac arrest is unknown. Methods: This study represents analysis of data from the prospective multicenter Pediatric Intensive Care Quality of cardiopulmonary resuscitation (PICqCPR) Study. Primary predictor variables were median DBP and median systolic blood pressure (SBP) over the first 10 min of CPR. The primary outcome measure was "new substantive morbidity" determined by Functional Status Scale (FSS) and defined as an increase in the FSS of at least 3 points or increase of 2 in a single FSS domain. Univariable analyses were completed to investigate the relationship between new substantive morbidity and BPs during CPR. Results: 244 index CPR events occurred during the study period, 77 (32%) CPR events met all inclusion criteria as well as having both DBP and FSS data available. Among 77 survivors, 32 (42%) had new substantive morbidity as measured by the FSS score. No significant differences were identified in DBP (median 30.5 mmHg vs. 30.9 mmHg, p = 0.5) or SBP (median 76.3 mmHg vs. 63.0 mmHg, p = 0.2) between patients with and without new substantive morbidity. Children who developed new substantive morbidity were more likely to have lower pre-arrest FSS than those that did not (median [IQR]: 7.5 [6.0–9.0] versus 9.0 [7.0–13.0], p = 0.01). Conclusion: New substantive morbidity determined by FSS after a pediatric IHCA was associated with baseline functional status, but not DBP during CPR.